Strategi Pencegahan Kejahatan oleh Bank X dalam Menghindari Kejahatan Perbankan melalui Mesin Anjungan Tunai Mandiri (ATM) - Rahardika Nugroho; Muhammad Zaky (Universitas Budi Luhur, 2019)
Final Project (Thesis) discusses crime prevention strategies as one of the state-owned banks to avoid crime in the banking world by utilizing ATM machines as a means to commit crime. One of the crimes is skimming which is a form of virtual crime by utilizing computer media connected to the internet. The perpetrators committed this crime by placing a small camera on the hand cover on the ATM machine. CCTV installed on an ATM machine is very useful for recording what happens at the ATM machine and can report it to the relevant bank. Situational prevention by checking the environment as well as the survey when the ATM machine was placed by Bank Mandiri was to prevent the risk of skimming crimes using their ATM machines. Routine checks carried out by Bank Mandiri on their ATM machines to see whether there are foreign equipment and foreign objects installed on their ATM machines. Checks carried out by the bank Mandiri to avoid any foreign objects found on the ATM machine. Bank Mandiri calls on customers to contact the call center if they experience problems with the ATM machine.